TiO2 thin film growth using the MOCVD method - Bernardi, M.i.b. (2001)
Titanium oxide (TiO2) thin films were obtained using the MOCVD method. In this report we discuss the properties of a film, produced using a ordinary deposition apparatus, as a function of the deposition time, with constant deposition temperature (90 °C), oxygen flow (7,0 L/min) and substrate temperature (400 °C). The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and visible and ultra-violet region spectroscopy (UV-Vis). The films deposited on Si (100) substrates showed the anatase polycrystalline phase, while the films grown on glass substrates showed no crystallinity. Film thickness increased with deposition time as expected, while the transmittance varied from 72 to 91% and the refractive index remained close to 2.6.